Implikasi Yuridis Keputusan Non Kuorum Majelis Kehormatan Notaris dalam Proses Pemeriksaan Notaris - Hasibuan, Rizky Zulkarnain; Widagdo, Setyo; Kawuryan, Endang Sri (Universitas Negeri Malang, 2021)
This study aimed to analyze the juridical implications of non-quorum decisions of the Notary Assembly in the notary examination process and legal protection for notaries for non-quorum decisions of the Notary Honorary Council. The study used normative juridical, with statutory and conceptual approaches. This study discussed law as a norm or rule that applied in society and was used as a behavioural guide for everyone. The study results showed that the juridical implications of non-quorum decisions of the Notary Assembly in the notary examination process were null and void after a court decision had permanent legal force. The decision was declared legally invalid so that it cannot be applied to the notary concerned. Legal protection for notaries for non-quorum decisions of the Notary Honorary Council was obtained by filing an administrative objection to the State Administrative Court by suing the Notary Assembly.